2022
DOI: 10.1002/aepp.13233
|View full text |Cite
|
Sign up to set email alerts
|

U.S. agricultural university students' mental well‐being and resilience during the first wave of COVID‐19: Discordant expectations and experiences across genders

Abstract: The coronavirus disease 2019 (COVID‐19) pandemic's first wave led to declining mental health and life satisfaction outcomes for college students, especially women. While women in undergraduate agricultural programs outperformed men academically prior to and during the pandemic, the achievement may have come at personal cost, especially for those women with fewer personal and environmental resiliency resources. Our research objective was to expand on personal, social, and environmental factors linked with lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 90 publications
0
6
1
Order By: Relevance
“…In other words, our analysis of this literature suggests that the inequities that are present in our broader world are reflected in online/remote learning settings. For example, Ehmke et al (2022) observed that as individuals' reported experiences with discrimination decreased, so did their mental health and their perceptions of online learning. They also observed the inverse, that women who experienced less or no discrimination did not experience a decline in mental health and also had more positive views of online learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, our analysis of this literature suggests that the inequities that are present in our broader world are reflected in online/remote learning settings. For example, Ehmke et al (2022) observed that as individuals' reported experiences with discrimination decreased, so did their mental health and their perceptions of online learning. They also observed the inverse, that women who experienced less or no discrimination did not experience a decline in mental health and also had more positive views of online learning.…”
Section: Discussionmentioning
confidence: 99%
“…Echoing similar themes as Apgar and Cadmus (2022), other studies of mental health during the pandemic also similarly noted that on-campus students were experiencing declining mental health and quality of life. As a few examples, Amerson et al (2021) described this phenomenon in nursing programs, Ehmke et al (2022) focused on women in agricultural science programs, and Gusman et al (2021) explored a general undergraduate population. In light of the pre-pandemic evidence of a growing problem with mental health and well-being for on-campus, in-person learners, it is reasonable to infer that there are significant factors besides learning modality that impact student mental health.…”
Section: Context and Review Of Relevant Literaturementioning
confidence: 99%
“…We add to the exploration of how AI-driven innovations are enhancing research capabilities, facilitating the dissemination of knowledge, and redefining pedagogical strategies. Our research contributes to the growing body of knowledge aimed at understanding and improving educational outcomes in the economics, agricultural economics, and agribusiness disciplines (Ehmke et al, 2022;House et al, 2007;Kiesel et al, 2021Kiesel et al, , 2020Offutt & McCluskey, 2022;Zuo et al, 2019). By examining a specific application and real-world examples of AI capabilities, we illuminate the ways in which AI technologies are optimizing learning experiences and empowering educators and students in the domain of agricultural economics.…”
mentioning
confidence: 88%
“…These disruptions have affected student outcomes and preferences for learning such as the ability to attend classes (and college in general), and mental health and well‐being (Ehmke et al, 2022; Jaggars et al, 2020; Lederer et al, 2021; Soria et al, 2020). The pandemic also raised discussions concerning the value of residential and on‐campus experiences (Aucejo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%